Analisis Tokoh Utama Dalam Cerpen Atsim Al-Hawa’ Karya Ibrahim Al-Syamlan Kajian Psikoanalisis Sigmund Freud - Chairani Soleha (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
This study aims to analyze the main character in the short stories Atsim al-Hawa' by Ibrahim al-Syamlan based on the psychoanalytic theory of Sigmund Freud's perspective. This research is a qualitative descriptive study. The main data is the short story Atsim al-Hawa' by Ibrahim al-Syamlan. Data collection techniques are reading and taking notes. Data analysis techniques in this study used the interactive method. The results of the study are: The main character Sarrah has a personality conflict based on id, ego, and superego. The id creates feelings of sadness, anxiety, pleasure, and obsession. The ego is aware of it to accept reality and avoid the influence of the id. and the superego creates feelings of regret and guilt. the id aspect dominates Sarrah's character, made her is more influenced by the subconscious.